Patterns of text : in honour of Michael Hoey - Hoey, Michael; Scott, Mike, 1946-; Thompson, Geoff, 1947- (John Benjamins Pub. Co., 2001)
It is increasingly clear that, in order to understand language as a phenomenon, we must understand the phenomenon of text. Our primary experience of language comes in the form of texts, which embody the complete communicative events through which our language-using lives are lived. These events are shaped by communicative needs, and this shaping is reflected in certain characteristic patterns in the texts. However, the nature of texts and text is still elusive: we know which forms are typically found in text but we do not yet have a full grasp of how they constitute its textuality, how they ma.